PELATIHAN PENYUSUNAN INSTRUMEN PENILAIAN BERBASIS HOTS BAGI GURU DI SDN 09 KAMPUNG MELAYU - Lora Devian; Desyandri (STKIP Subang, 2022)
A quality learning assessment instrument is a measuring tool to determine student learning outcomes. This HOTS-based assessment instrument preparation training aims to improve the ability of SDN 09 Kampung Melayu teachers in developing HOTS-based assessment instruments. This training activity is urgently needed by teachers due to the low competence of teachers in designing assessment instruments according to curriculum standards. Through this activity the teachers provide insight as well as technical skills in preparing assessment instruments. This training activity is divided into five parts, namely pre-test, exploration, elaboration, confirmation and post-test activities. In the pre-test stage the participants worked on questions related to HOTS-based assessments, in the exploration stage the resource persons conducted brainstorming with participants related to HOTS-based assessments. After brainstorming, the informants carried out elaboration activities, namely explanatory material regarding the preparation of HOTS-based assessment instruments. At the confirmation stage, the training participants were directed to form groups and hold discussions in preparing HOTS-based assessment instruments. The next stage is the group representative showing the results of the discussion in front of the other groups. In the post-test stage the participants worked on questions related to the training material with the result that there was an increase in the post-test score with an increase in value of 59.52% where the average post-test score increased to 74.60 from the pre-test average score 44.40 so that it can be interpreted that the results of this training can significantly increase the knowledge of SDN 09 Kampung Melayu teachers in designing HOTS-based assessment instruments.